SKRINING FITOKIMIA DAN UJI TOKSISISTAS EKSTRAK ETANOL DAUN SUTRA PERSIA (Albizia julibrissin) - Mohammad Alvian Noor Arya; Renety Oktaviani; Nurul Aisyah; Madya Saputri; Imel Utami Pairunan; Yonathan Desmellson Situmorang; Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Persian silk (Albizia julibrissin) is a medicinal plant known to contain active compounds such as alkaloids, phenolics, flavonoids and quinones which have the potential as antioxidants and natural toxic compounds. Phytochemical screening showed the presence of these compounds in the leaf extract. In addition, a toxicity test using the Brine Shrimp Lethality Test (BSLT) method on Artemia salina larvae showed that the extract had an LC₅₀ value of 0.000007 ppm, which is included in the very toxic category. These results indicate that Persian silk leaves (Albizia julibrissin) have the potential to be developed as natural bioactive agents. Keywords: Sutra Persia, Phytochemical Screening, Brine Shrimp Lethality Test (BSLT)